An Assessment of the Relation between Quality of Life and Satisfaction in Domains of Life in Chennai City – An Empirical study - Mookambika BA, D. Jayanthi (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Quality of life (QoL) is exposed as the satisfaction which a person acquires from its surrounding of physical conditions and human conditions that were scale dependent. This QoL could predominantly impact the behaviour of groups inclusive of economic units (firms) and households and individual persons. QoL turns out as theoretically and empirically researched term, in urban planning stream. Specifically in a sector of urban regeneration, the progressing interest lead primarily from unique fact that this QoL contribute to have effects upon cities effective development. The previous literature delineated that certain considerations of QoL could play a significant role to improvise their standards, when organisation and households decide to reside on a location. The direction of this research relies in the investigation of urban planning and regeneration literatures, and to incorporate QoL considerations, in different domains of life into sustainable living standards in measuring through their satisfaction range. The primary objective of the research the key elements, influencing the QoL of people, residing in the sub-cities of Chennai such as Mylapore, Sholinganallur and T.Nagar were determined and the corresponding satisfaction levels in different domains of life are acquired from 957 household participants. The data collection, accomplished through structured questionnaire, gathered from survey assessment, wherein the population samples are chosen using stratified random sampling-approach. The quantitative analysis is employed to assess the association of these life domain attributes and the QoL in terms of levels of satisfaction, from the respondents, through SPSS software package. The research could aid in understanding QoL of urban populations and their domains, and to evaluate the same in regions having similar socio-economic and geographic environment.